G-Quadruplexes in RNA biology: recent advances and future directions (2020)
RNA G-quadruplexes (RG4s) are four-stranded structures known to control gene expression mechanisms, from transcription to protein synthesis, and DNArelated processes. Their potential impact on RNA biology allows these structures to shape cellular processes relevant to disease development, making their targeting for therapeutic purposes an attractive option. We review here the current knowledge on RG4s, focusing on the latest breakthroughs supporting the notion of transient structures that fluctuate dynamically in cellulo, their interplay with RNA modifications, their role in cell compartmentalization, and their deregulation impacting the host immune response. We emphasize RG4- binding proteins as determinants of their transient conformation and effectors of their biological functions.